2015
DOI: 10.1016/j.compedu.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of students' lived experiences of using smartphones in diverse learning contexts using a hermeneutic phenomenological approach

Abstract: -Gleaves, A. (2015) 'An exploration of students' lived experiences of using smartphones in diverse learning contexts using a hermeneutic phenomenological approach. ', Computers and education., Further information on publisher's website:http://dx.doi.org/10. 1016/j.compedu.2014.11.001 Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Computers and Education. Changes resulting from the publishing process, such as peer review, editing, correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 45 publications
2
50
0
13
Order By: Relevance
“…Most research literature reveals generally positive outcomes and attitudes to m-learning [28]. This study showed that higher level of self-efficacy results in higher levels of performance expectancy, social influence, and effort expectancy, which support higher behavioral intention.…”
Section: Discussionsupporting
confidence: 54%
“…Most research literature reveals generally positive outcomes and attitudes to m-learning [28]. This study showed that higher level of self-efficacy results in higher levels of performance expectancy, social influence, and effort expectancy, which support higher behavioral intention.…”
Section: Discussionsupporting
confidence: 54%
“…In this study, it is found that most of the language learning is incidental or serendipitous learning (Chan et al 2015;Jones et al, 2014). Participants reported that their language learning were mostly at awareness level and were prompted by the motivation to learn basic phrases and sentences for their interactions with friends or teachers.…”
Section: Discussion: the Nature Of Language Learning Using Smartphonesmentioning
confidence: 92%
“…Some of the purposive learning practices described by participants have a planned element (Chan et al, 2015). They would deliberately put aside their leisure time to learn languages, either to improve their English Language proficiency or to practice pronunciation of a target language that they were currently learning.…”
Section: Discussion: the Nature Of Language Learning Using Smartphonesmentioning
confidence: 99%
“…Utilising the theoretical principles and practices of hermeneutic phenomenology, this study aimed to gain access to a phenomenon that is often subconscious in order to understand the nature and meaning of the participants' lived experiences. The interpretation of the texts of life was expected to yield rich and detailed descriptions of workplace spirituality in women leadership in South African HEIs (Chan, Walker and Gleaves 2015;Creswell 2015;Fossey et al 2002). The concept of Dilthey's modern hermeneutics (2002) was used to create 'Verstehen' (understanding) of workplace spirituality in women leadership in HEIs.…”
Section: Methodsmentioning
confidence: 99%